Incidence of Major Depressive Disorder: Variation by Age and Sex in Low-Income Individuals: A Population-Based 10-Year Follow-Up Study. Issue 15 (April 2016) - Lee, Chun-Te; Chiang, Yi-Cheng; Huang, Jing-Yang; Tantoh, Disline M.; Nfor, Oswald N.; Lee, Jia-Fu; Chang, Cheng-Chen; Liaw, Yung-Po
Abstract : Abstract: Major depressive disorder (MDD), the most prevalent mental disorder is a global public health issue. The aim of this study was to assess the association between low income and major depressive disorder (MDD) by age and sex. The National Health Insurance Research Database (NHIRD) of Taiwan was used to retrieve data. A total of 1, 743, 948 participants were eligible for the study. Low-income individuals were identified from 2001 and 2003 (specifically, Group Insurance Applicants, ie, category"51" or "52") and followed from 2004 to 2010. MDD was identified using the ICD-9-CM 296.2 and 296.3 codes. Among non-low-income individuals, the MDD incidence rates increased with age in both males and females, that is, 0.35, 0.93, 0.97, 1.40 per 10, 000 person-months for males and 0.41, 1.60, 1.89, 1.95 per 10, 000 person-months for females aged 0 to 17, 18 to 44, 45 to 64, and ≥65 years, respectively. Low-income females (18–44 years) and males (45–64 years) had the highest incidence of MDD, which was 3.90 and 3.04, respectively, per 10, 000 person-months. Among low and non-low-income individuals, the MDD incidence rates were higher in the females than males in all age groups. Males aged 45 to 64 and 0 to 17 years had highest hazard ratios (HR) of 2.789 (95% confidence interval [CI], 1.937–4.014) and 2.446 (95% CI, 1.603–3.732), respectively. The highest HRs for females were 2.663 (95% CI, 1.878–3.775) and 2.219 (CI, 1.821–2.705) in the 0 to 17 and 18- to 44-year age groups. Low income was not found to serve as a risk factor for the development of MDD in males and females aged ≥65 years. Among the non-low-income males and females, the incidence rates of MDD were found to increase with age. Low income was found to serve as a significant risk factor for MDD only in individuals under age 65.